(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The study aimed to identify strategic entrepreneurship and its role in enhancing `creative behavior in the Bagdad Soft Drinks Company. Strategic entrepreurship was measured as an independent variable through six dimensions : (entrepreneurial culture, entrepreneurial leadership, strategically managed resources, enterprtneurial mind, risk tolerance, and creativity) , Innovative behavior was measured as a dependent variable through five dimensions (originality, fluency, Flexibility, sensitivity to problems, and details) The study started from a basic problem represented by several questions revolving around the nature of the influential relationship between its variables in the field impact of strategic entrepreurship on innovative behavior and its dimensions according to the study . The study deriver its importance from the company’s ability to improve its behavior. Innovative innovation begins with strategic entrepreneurship. In order to reach the results, the study relied on the descriptive analytical approach in collecting and interpreting date, and relied on the likert scale, and used several statistical methods, the most important of which are (Person’s correlation coefficient, structural equation modeling with partial least squares pls – sem, the F test, and the T test. As for the most prominent statistical processing the data is (Spss v-26, Smart pls v.4.0.8.4, Microsoft Excel 2016(. The study reached a set of results, the most prominent of which was: There is a positive and significant relationship between the variable of strategic entrepreneurship and the variable of innovative behavior, As well as between the dimensions of each of them. The study came up with a number of recommendations, the most important of which is that the company’s management should increase attention to the dimensions of strategic entreneurship because it will increase the ability to enhance innovative behavior to achieve success and creativity in prosperity and growth of the company.